The Jurassic-Cretaceous Paleogeography Of The Sula Area, North Maluku - Eko Budi Lelono; Irwansyah Irwansyah; Panuju Panuju (Testing Center for Oil and Gas LEMIGAS, 2011)
The study of paleogeography and hydrocarbon potentiality of the Sula area, North Maluku has been conducted by the Lemigas Exploration team. This paper specifically presents a paleogeography of the Jurassic-Cretaceous age of the Sula area as a part of the result of this study. In this paper, paleogeography means palaeoenvironment which is defined based on biostratigraphy. Data used in this paper are mostly secondary data obtained from National Data Center which is combined with primary data collected during field work campaign. The subsurface data analysis allows subdivision of 7 depositional sequences throughout Jurassic-Cretaceous succession. In fact, each sequence mostly consists of transgressive and highstand system tracts. Lowstand system tract only occurs in the earliest sequence. Sequences 1 (Bobong Formation), 2, 3 and 4 (Buya Formation) are assigned to the Jurassic age, whilst sequences 5, 6 and 7 (Buya Formation) are attributed to the Cretaceous age. Generally, the depositional environment of most sequences is getting deeper toward the North. The shallowest environment takes place in non-marine setting, whereas the deepest environment occurs in outer neritic (100m-200m). It is most likely that Jurassic-Cretaceous depocenter was situated in the northern part of the study area. However, it is required additional data to confirm this interpretation.